Opening pathways to training for young disabled dancers: an action research approach. Issue 4 (2nd October 2021) - Aujla, Imogen
Abstract : There are numerous barriers to dance for disabled people but one which has received increasing attention in recent years is the lack of systematic training available. The aim of this project was to explore how private dance studio syllabi could be made more accessible for young disabled people, in order to open pathways to dance. Three private studio teachers were matched with three specialists in inclusive dance to translate particular syllabi for their groups of disabled learners. Various actions and strategies were designed by the teachers and specialists, which were reviewed and revised over the course of the project. Data collection included class observations, interviews with the teachers, specialists, young dancers, and their parents, and online diary entries by the teachers and specialists after each class. Analyses revealed that while each group was unique, common strategies included determining the key principles of each exercise, differentiation, setting high expectations, and a flexible class structure. Multiple forms of improvement among the participants were noted, including increased teacher confidence, and improvements in students' technical abilities, confidence, and social skills. Overall, the findings of this study attest to both the viability and value of providing progression opportunities for young disabled dancers.